2010
DOI: 10.4088/jcp.09m05731blu
|View full text |Cite
|
Sign up to set email alerts
|

Becoming the Center of Attention in Social Anxiety Disorder

Abstract: Objective A detailed understanding of how individuals diagnosed with social anxiety disorder (SAD) respond physiologically under social-evaluative threat is lacking. We aimed to isolate the specific components of public speaking that trigger fear in vulnerable individuals and best discriminate among SAD and healthy individuals. Method Sixteen individuals diagnosed with SAD and 16 healthy individuals were asked to prepare and deliver a short speech in a virtual reality (VR) environment. The VR environment sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The present study examined more specific variation in anxiety phenomenology, and results indicated that social phobia symptoms specifically were associated with heightened startle potentiation in anticipation of unpredictable threat. Social phobia has previously been associated with an increased startle reflex during fearful imagery (McTeague et al, 2009), anticipation of public speaking (Cornwell et al, 2011, 2006), and across an entire task (Larsen, Norton, Walker, & Stein, 2002). However, the present study is the first to demonstrate an association between social phobia symptoms and startle potentiation as a function of the predictability of threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined more specific variation in anxiety phenomenology, and results indicated that social phobia symptoms specifically were associated with heightened startle potentiation in anticipation of unpredictable threat. Social phobia has previously been associated with an increased startle reflex during fearful imagery (McTeague et al, 2009), anticipation of public speaking (Cornwell et al, 2011, 2006), and across an entire task (Larsen, Norton, Walker, & Stein, 2002). However, the present study is the first to demonstrate an association between social phobia symptoms and startle potentiation as a function of the predictability of threat.…”
Section: Discussionmentioning
confidence: 99%
“…The age range of the sample spanned late childhood and early adolescence, a period during which there is a marked increase in social phobia (Beesdo et al, 2009; Merikangas et al, 2010). Importantly, social phobia has been previously linked to intolerance of uncertainty (Boelen & Reijntjes, 2009; Carleton, Collimore, & Asmundson, 2010; Whiting et al, 2014) and an increased startle reflex in anticipation of public speaking (Cornwell, Heller, Biggs, Pine, & Grillon, 2011; Cornwell, Johnson, Berardi, & Grillon, 2006), an uncertain and unpredictable threat. Therefore, it was hypothesized that greater social phobia symptoms would be associated with increased startle and self-reported anxiety in anticipation of unpredictable (but not predictable) threat.…”
mentioning
confidence: 99%
“…In the subsequent appraisal stage, anxious individuals are likely to regard ambiguous and threatening stimuli (e.g., mild electric shocks in the laboratory and motor vehicle accidents in real life) as more threatening than they actually are (Boddez et al, 2012; Britton et al, 2011; Dash and Davey, 2012; Lazarus and Folkman, 1984; Meiser-Stedman et al, 2009). This may contribute to the tendency for anxious individuals to show greater neurobiological reactivity to standardized threatening stimuli such as a virtual audience for a public speaking task or angry and fearful human faces (Cornwell et al, 2011; Eldar et al, 2011; Robinson et al, 2012a). Finally, following such reactions, anxious individuals engage in cognitive-behavioral avoidance of perceived threats, which limits their ability to challenge inappropriate threat perception, confront and resolve threatening situations, and reshape expectations for the future (Cisler and Koster, 2010; Koster et al, 2006).…”
Section: Neurobiological Sensitivity To Threatmentioning
confidence: 99%
“…What is perhaps more relevant in this context is the fact that the VR environment have been shown to have a specific effect on clinical subjects (i.e., those that had a social anxiety disorder diagnosis) as compared to healthy controls. In a recent study, subjects with social anxiety showed higher overall state anxiety during the entire procedure (entering VR environment, performing a speech and existing the environment) and higher startle responses in the anticipation phase in which the virtual audience turned towards the subjects (Cornwell, Heller, Biggs, Pine, & Grillon, 2011). Given these findings, we believe that the use of VR could overcome potential limitations of the emotion regulation paradigm.…”
Section: Virtual Reality and Basic Research In Anxiety Disordersmentioning
confidence: 82%